THE EFFECT OF HEALTH EDUCATION THROUGH SESSION-HEALTH APPLICATION MEDIA ON BEHAVIOR MANAGEMENT BEHAVIOR OF DIABETES MELITUS IN BENGKULU CITY - Hanifah Hanifah; Vike Pebri Giena; Ruri Maiseptya Sari (Nurse and Health: Jurnal Keperawatan, 2019)
Background: Diabetes mellitus (DM) is a chronic disease that requires specific self-management behavior for a lifetime, to avoid long-term diabetic complication. Education about diabetes self-management for people with diabetes mellitus and families is absolutely necessary to overcome diabetic complications. The use of smartphones as educational media provides space for people with DM without restrictions on place and time.Objective: The aims of this study was to identify the effect of health education through the Salam-Sehat application media on diabetes self-management behavior.Method: This research is quantitative with pre-experiment design with one group pre-test post-test. The population of this study was all people with DM in Bengkulu City. Sample was selected by using Multi Stages Cluster Sampling technique. The sample size was determined using the Slovin formula which results are 384 respondents. The sample was selected by using proportional random sampling. The Data were analyzed by using the Wilcoxon Signed Rank Test.Result: The results showed that the average DM self-management behavior before being given education through the Salam-Sehat application was 35.42 and the average DM self-management behavior after being given education through the Salam-Sehat application was 65.18. There is significant influence of health education through Salam-Sehat application media for self-management behavior among diabetes mellitus people in Bengkulu City, with Asymp value. Sig (p) = 0.000.Conclusion: It is expected that the research results of the Salam-Sehat application can be used as an online-based health education media that provides convenience in obtaining health information without being limited by space and time for people with DM in Bengkulu City. Key words: Diabetes Mellitus, Self-Management, Application.